Effects of hydrogen peroxide and calcium hypochlorite on chemical oxygen demand solubilization and disintegration of waste activated sludge by electro-chemical pretreatment - Erkan, Hanife Sari; Turan, Nouha Bakaraki (TAYLOR & FRANCIS LTD, 2024)
The combination of electrochemical (EC) pretreatment with hydrogen peroxide (HP) and calcium hypochlorite (CHC) was investigated in this study for their effect on soluble chemical oxygen demand (CODs) and disintegration degree (DD) of waste activated sludge (WAS). For this aim, response surface methodology (RSM) and Box-Behnken design (BBD) were applied the determination of the optimum operational conditions. Operational conditions were varied between 0.2 and 2.0 mmol/g SS for HP and CHC dosages, 1-5 A for the applied current, 2-10 for the initial pH, and 15-45 min for the treatment time. Obtained results for each treatment were accurate and significant with correlation coefficients (R2) of 0.8639% and 0.9189% for EC combined with HP pretreatment and EC combined with CHC pretreatment, respectively. According to the obtained results, CODs increased in comparison to the raw sludge (168 mg/L) noting that CODs for EC - CHC (1155 +/- 21 mg/L) was higher than EC - HP (811.5 +/- 15 mg/L) at optimized conditions (for EC-HP pretreatment: HP dosage: 0.34 mmol/g TSS, Applied current:5 A, Initial pH:10, Time: 45 min, For EC-CHC pretreatment: CHC dosage: 0.23 mmol/g TSS, Applied current:4.83 A, Initial pH:10, Time: 40 min). Besides, the DD in terms of COD, total nitrogen (TN) and total organic carbon (TOC) (DDCOD, DDTN and DDTOC) registered increased values after the application of the EC treatment with both oxidants. The highest DDCOD, DDTN and DDTOC values were obtained with EC-CHC pretreatment for 11.34%, 20.34% and 9.18% respectively compared to EC-HP pretreatment (DDCOD: 7.37%, DDTN: 15.18% and DDTOC: 6.94%). [GRAPHICS] .
Keywords: Electro-chemical treatment; disintegration; extracellular polymeric substances; hydrogen peroxide; calcium hypochloride; ANAEROBIC-DIGESTION; CONDITIONING PROCESS; EXCESS SLUDGE; SEWAGE-SLUDGE; DEWATERABILITY; OXIDATION; ENHANCEMENT; ELECTROCOAGULATION; PEROXYMONOSULFATE; OPTIMIZATION; Environmental Sciences & Ecology